Simulation analysis of prestressed tensioning whole processon direct constraint method - Kaimin Liu (Functional Materials, 2017)
The accuracy simulation of the prestressed tensioning effect is the foundation of prestressed bridge design, construction and reinforcement. Direct constraint method was used in the application of prestressed tensioning whole process simulation analysis on the background of prestressed testing experiment. Its aim was to achieve the real simulation of interaction between prestressed tendon and concrete in the tensioning whole process. Three-dimensional solid elements were adopted to simulate pre-stressed reinforcement unit and concrete unit. Bilinear Coulomb friction was adopted as the friction form between prestressed tendon and concrete. Direct constraint method that has the characteristics of good stability and fast convergence speed was used to calculate the effective stress of prestressed tendon at each tension stage. The loss of one-way stress was also calculated. The effective prestressed values by simulation on direct constraints method can be well with the measured values and the theoretical values on Code for Design of Highway Reinforced Concrete and Prestressed Concrete Bridges and Culverts. The method has theoretical basis on accurately simulating the actual stress in different stages of the prestressed tendon. It can be helpful for bridge design and reinforcement.